Decomposition of trimethylgallium and adduct formation in a metalorganic vapor phase epitaxy reactor analyzed by high‐resolution gas monitoring system. Issue 8 (28th June 2017) - Nagamatsu, Kentaro; Nitta, Shugo; Ye, Zheng; Nagao, Hirofumi; Miki, Shinichi; Honda, Yoshio; Amano, Hiroshi
Abstract : In this study, by using time‐of‐flight (TOF) high‐resolution and high‐sensitivity mass spectrometry measurements, the decomposition of trimethylgallium into dimethylgallium and monomethylgallium along with its adduct formation with NHx in a commercially available horizontal metalorganic vapor‐phase epitaxy (MOVPE) reactor with a resistive heater was investigated and observed in more detail than previously reported. The results confirmed the use of the TOF monitoring system in analyzing the elementary reaction process in actual MOVPE systems.